Influência do uso e ocupação da terra na dinâmica do rio São Lourenço - estado de Mato Grosso - Carlini, Elisa Racy [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This study aims to analyze the relationship between deforestation in the highlands of the São Francisco River Basin over the past 45 years due to agricultural activities and livestock , and the observed changes in the dynamics of the same river in the Pantanal of Mato Grosso , as sinuosity , discharge sediment , flow, points of erosion and morphological changes . It is observed that deforestation occurs in the plain and on the plateau , however with much more intensity in the latter, provided the extensive land use in the region . Thus, the study aims to contribute to a better understanding of the relationships between the uplands and flood plains . To achieve this goal will be used proper methods of geomorphological and geological sciences , with emphasis on the use of satellite imagery and hydrological data side . The research will include the following steps : I) literature review ; II) characterization geomorphological , geological , hydrological and climate , III) Dynamics of vegetation ; IV) Analysis of cause-effect relationships in the river system . Product analysis will suggest preventive measures to minimize the effects caused by the practices of use and occupation in the study area, as well as other regions suffer the same impacts

O presente trabalho visou analisar a relação entre o desmatamento no planalto da Bacia do Rio São Lourenço nos últimos 45 anos, devido às atividades de agricultura e pecuária, e as mudanças observadas na dinâmica do mesmo rio no Pantanal Mato-Grossense, como sinuosidade, descarga de sedimentos, vazão, pontos de erosão e mudanças morfológicas. Observou-se que o desmatamento ocorre na planície e no planalto, no entanto, com muito mais intensidade no último, proporcionado pelo extenso uso da terra na região. Desta maneira, o estudo objetivou contribuir com a melhor compreensão das relações entre os planaltos e a planície pantaneira. Para atingir tal objetivo foram utilizados métodos próprios das ciências geológicas e geomorfológicas, com ênfase no uso de imagens de satélite e dados hidrológicos secundários. A pesquisa compreendeu as seguintes etapas: I) revisão bibliográfica; II) caracterização geomorfológica, geológica, hidrológica e climática; III) Dinâmica da cobertura vegetal; IV) Análise das relações de causa-efeito no sistema fluvial. A análise do produto permitiu sugerir medidas preventivas e de minimização dos efeitos provocados pelas práticas de uso e ocupação na área estudada, assim como em outras regiões que sofrem os mesmos impactos
Keywords: Geomorfologia; Solo - Uso; Desmatamento; São Lourenço, Rio, Bacia (MT)